Perbandingan Tingkat Kesembuhan Luka pada Kulit Kelinci yang Dijahit Benang Bedah Absorbable (Catgut) dan Nonabsorbable (Silk) (COMPARISON OF WOUND HEALING LEVELS ON RABBIT SKIN SUTURED WITH ABSORBABLE (CATGUT) AND NONABSORBABLE (SILK) SURGICAL THREAD) - Sudira, I Wayan; Dada, I Ketut Anom; Gustara, I Wayan Mas Adi (Jurnal Veteriner, 2019)
This research’s purpose was to compare the level of wound recovery between sewn rabbit skin with absorbable thread (monofilamen) and nonabsorbable (multifilamen) then observed macroscopicly. This research used 16 male rabbit in 2 – 3 kg. Before surgery begins, the rabbits wtRe.anesthisad with ketamine-xylazine and then surgical action follows after that by making incision wound at left and right back with 3 cm long and the depth up to subcutan line. Right back is sewn by absorbable thread (catgut 3.0) and left back is sewn by nonabsorbable (silk 3.0). From the results of the study the using of absorbable threads (catgut) and nonabsorbable (silk) of the four parameters observation can be summarized that the: scab marks show better results on the use of catgut threads indicating that the process of wound healing is faster.